Sustainable Coastal Tourism Planning in Mursala Island, Central Tapanuli Regency - Irwan Sutiono; Cut Nuraini; Abdi Sugiarto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Mursala Island is one of the potential coastal tourism areas in Central Tapanuli Regency, known for its natural uniqueness and rich local culture. However, tourism development in this area re-mains unstructured and unsustainable. This study aims to analyze the current conditions, infrastructure readiness, accessibility, community participation, and the level of local socio-cultural resilience toward tourism in order to formulate strategies for sustainable coastal tourism development. A mixed-methods approach was employed, with primary data collected through observation, in-depth interviews, and a questionnaire distributed to 100 respondents.The results show that local socio-cultural resilience is the most strategic variable in supporting tourism interest (mean = 4.06), followed by community participation (3.82), infrastructure readiness (3.61), and accessibility (3.26). Qualitative findings reinforce these results, revealing that while the community actively maintains cultural traditions, they face access barriers and lack participatory institutions. A SWOT analysis led to realistic strategies such as establishing a Local Customary Tourism Unit, developing permanent piers and sea transportation, and drafting a village regulation (Perdes) on culture-based tourism.This study concludes that sustainable coastal tourism development in Mursala Island must be grounded in the strength of local social capital, cultural preservation, and improvements in accessibility and infrastructure. The findings contribute theoretically to strengthening the concept of Community-Based Tourism (CBT) and practically to informing policy direction for locally-based coastal tourism area development.